Domestically Acquired Seoul Virus Causing Hemophagocytic Lymphohistiocytosis—Washington, DC, 2018. (21st September 2019) - Shastri, Bhagyashree; Kofman, Aaron; Hennenfent, Andrew; Klena, John D; Nicol, Stuart; Graziano, James C; Morales-Betoulle, Maria; Cannon, Deborah; Maradiaga, Agueda; Tran, Anthony; Ramdeen, Sheena K
Abstract: Seoul orthohantavirus (SEOV) infections, uncommonly reported in the United States, often result in mild illness. We report a case of hemophagocytic lymphohistiocytosis secondary to SEOV infection that was domestically acquired in Washington, DC.